2016
DOI: 10.1142/s1793545816500164
|View full text |Cite
|
Sign up to set email alerts
|

Automatic counting method for complex overlapping erythrocytes based on seed prediction in microscopic imaging

Abstract: Blood cell counting is an important medical test to help medical sta®s diagnose various symptoms and diseases. An automatic segmentation of complex overlapping erythrocytes based on seed prediction in microscopic imaging is proposed. The four main innovations of this research are as follows: (1) Regions of erythrocytes extracted rapidly and accurately based on the G component.(2) K-means algorithm is applied on edge detection of overlapping erythrocytes. (3) Traces of erythrocytes' biconcave shape are utilized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Python3 libraries such as NumPy, SciPy, scikit-learn, Keras, pandas, and Matplotlib are utilized to perform the categorization through ML models. Scikit-learn appears to be the most user-friendly and reliable machine learning library [49,50]. e foundations of this package are NumPy, SciPy, and Matplotlib.…”
Section: Methodsmentioning
confidence: 99%
“…Python3 libraries such as NumPy, SciPy, scikit-learn, Keras, pandas, and Matplotlib are utilized to perform the categorization through ML models. Scikit-learn appears to be the most user-friendly and reliable machine learning library [49,50]. e foundations of this package are NumPy, SciPy, and Matplotlib.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure (Fig. 2) is inspired by the one described by Wei and Cao (2016), consisting in smoothing the image using a mean filter, then the application of a threshold separating the pores and the matrix, and finally the watershed treatment available in ImageJ in order to get the surface area and the coordinates of the centroid of each pore. The pores can be assimilated to perfect circles the diameters of which are calculated from Eq.…”
Section: Image Processingmentioning
confidence: 99%
“…From experiments, it was found that when the solid phase holdup reached 4.4%, the particle images overlapped significantly. The overlapped particle count is achieved by detecting the inner and outer edges of the overlapping particle image to find the concave point of the outer contour of the overlapping particle or the center point of the fitting circle, [22][23][24] but the selection of related algorithm parameters is sensitive, and it is easy to be disturbed by noise and cause the misdetection of the contour. Angst et al 25 used a threshold segmentation method to measure the gas phase holdup in a liquid-solid stirring system, but this method has a large error in the extraction of dim bubbles.…”
Section: Introductionmentioning
confidence: 99%